Psychological Disorders - Tariq, Ayesha (Pakistan Journal of Health Sciences, 2022)
Psychological disorder is referred to as a clinically significant disruption in a person’s behavior, cognition and emotional control. It is often linked to distress or functional impairment in key areas of brain functioning. Depression, bipolar illness, schizophrenia, and eating disorders are just a few examples of psychological problems. Psychological problems may be connected to several other conditions, such as insomnia, psychosis, stress, and anxiety. Different people are affected differently by these disorders and their severity might vary. Anxiety and depressive disorders are the most prevalent psychological illnesses, affecting 1 in 8 persons, or 970 million people worldwide [1]. Due to the COVID-19 pandemic, the number of individuals who suffer from anxiety and depression illnesses have greatly increased in 2020. Initial projections indicate a 26% and 28% rise in major depressive disorder and anxiety disorders in only one year [2]. In Pakistan, psychological problems represent more than 4% of all disease burden, with women’s mental health being greatly affected and neglected. According to estimates, 24 million Pakistanis need mental care and half of the population does not have access to the psychiatrists [3]. The likelihood of having psychiatric problems is influenced by a number of variables. Even while the majority of individuals are resilient, those who are exposed to unfavorable conditions, such as poverty, violence, handicap, and inequality, are more at risk. Individual psychological and biological characteristics, such as emotional skills and heredity may also increase risk of mental disorders. Changes in brain structure and/or function have an impact on several risk and protective factors. Pakistan, like other nations, has responded to the present COVID-19 outbreak on all fronts, including public health, but a number of difficulties must be addressed. Pakistan’s health-care system is poorly underfunded, and it does not meet the needs of people suffering from psychological disorders. There is a shortage of psychiatrists, and there is a significant gap between the demand for therapy and its supply. Even when assistance is provided, it is frequently of poor quality. People suffering from mental illnesses require social support, including assistance in forming and maintaining social, familial, and personal relationships. They also require aid with housing, employment, educational opportunities, and other enriching activities, for which specific institutions must be established.